Optimizing Secure Communication in Intelligent Transportation Networks with Certificate-less Authorization in VANETs - M. Shanthalakshmi; R.S. Ponmagal (International Journal of Computational and Experimental Science and Engineering, 2025)
As an outcome of technology progress, among the most widely used design models in intelligent transportation networks is Vehicular Ad-hoc Networks (VANETs). Assistance for Vehicle to Vehicle (V2V) connectivity is offered via VANETs. Automobile access to actual time traffic, weather, and transportation data is made possible via VANETs, which also assure traffic safety and effectiveness. The legitimacy of an organisation providing data is a crucial factor that must be taken seriously in order to ensure secure interaction in VANETs. In regards to safety mutual identification along with safe distribution of keys in VANETs continue to pose certain disadvantages considering that numerous protocols that have been suggested. However, since they depend on the authorised authority, they are susceptible to assaults through the firewall and Reliable Control (RC), which may raise safety issues amongst customers. we provide a certificate less secure authorization system that lessens the load on automobiles' internal storage and satisfies the delay criterion by doing away with certificate. The suggested system is strong and resistant against attacks from malevolent users